Avaliação do controle autonômico cardíaco e os efeitos de intervenções com e sem realidade virtual no desempenho motor em crianças com Transtorno do Desenvolvimento da Coordenação - Cavalcante Neto, Jorge Lopes (Universidade Federal de São Carlos, 2018)
Developmental coordination disorder (DCD) is a chronic condition characterized by significant motor impairment that interferes with functionality when performing academic, leisure and daily activities. Children with DCD have reduced motor skills and lower levels of social participation compared to their peers with typical development. Several restrictions regarding participation in group activities are documented since these children present with lower motivation in front of their more skilled peers. Due the restrictions in these different settings, children with DCD commonly present secondary consequences associated with their poor motor performance, such as cardiovascular dysfunction. Given the importance of motivational and effective interventions for children with DCD, previous studies have tested the effects of virtual reality (VR) training in order to improve their motor conditions. However, evidence with regard to the effects of VR training versus non-VR training, such as task-oriented training modalities, are still unclear. In addition, with respect to consequences regarding cardiovascular health, in particular cardiac autonomic control, studies to characterize this profile in children with DCD have not been conducted. Thus, this thesis consisted of four studies to shed light on unknown aspects regarding virtual reality training for children with DCD as well as their cardiovascular profiles with a focus on cardiac autonomic control. Study I, entitled ‘Linear and nonlinear analyses of the cardiac autonomic control in children with developmental coordination disorder: a case-control study’, aimed to assess cardiac autonomic control by linear and nonlinear analysis at supine and during orthostatic stimulus in DCD, at risk for DCD (r-DCD) and typically developed children. The results indicated blunted cardiac autonomic adjustment to the orthostatic stimulus and lower parasympathetic modulation in the supine position in children with DCD when compared with r-DCD and typically developed children. Study II, entitled ‘Is virtual reality effective in improving the motor performance of children with developmental coordination disorder? A systematic review’, aimed to synthesize evidence on the effectiveness of VR interventions for motor performance improvement in children with DCD. The results did not show enough evidence to support or refute the use of VR in order to improve motor performance in children with DCD. Study III, entitled ‘Motor intervention with and without Nintendo® Wii for children with developmental coordination disorder: protocol for a randomized clinical trial’, aimed to present a protocol to systematically compare the effects of two motor training programs (one Wii-based and the other non-Wii motor activities) on motor learning in children with DCD. The new protocol will help researchers and therapists to better understand the benefits of Wii-based motor intervention over those obtained with non-Wii interventions in children with DCD. In addition, the results from this intervention protocol will also create more systematized methods for replication in clinical practice. Finally, Study IV, entitled ‘Is Wii-based motor training better than matched task-specific training for children with developmental coordination disorder? A randomized controlled trial’, aimed to compare the relative efficacy of Wii-training versus non-Wii, task-specific training (TST) on movement skills by closely matching the type of motor activities selected for intervention. The results demonstrated similar benefits from both interventions, since all children with DCD who participated in Wii and TST groups improved significantly regarding their Movement Assessment Battery for Children – Second edition (MABC-2) total standard score. In addition, considering the MABC-2 components scores, Wii-based training had a more pronounced effect on manual dexterity while TST did for balance skills.
Assessment of cardiac autonomic control and the effects of intervention with and without virtual reality on motor performance in children with Developmental Coordination Disorder
Keywords: Transtorno do desenvolvimento da coordenação; Realidade virtual; Intervenção com Wii; Desempenho motor; Variabilidade da frequência cardíaca; Controle autonômico cardíaco; Developmental coordination disorder; Virtual reality; Wii training; Motor performance; Heart rate variability; Cardiac autonomic control; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL